Use of Human Chorionic Gonadotropin and Vaginal Progesterone Suppositories For Luteal Phase Support in Gonadotropin-Induced Cycles: A Comparative Study - Emel Ebru Özçimen; Mustafa Uğur; Dilek Uygur; Necati Özçimen; Zarif Yılmaz (Medical Network, 2006)
OBJECTIVE: To determine the efficacy of luteal phase support with human chorionic gonadotropin (hCG) or micronised progesterone (MP) during exogenous gonadotropin induced cycles. STUDY DESIGN: A prospective randomised cross ov er study was perf ormed to ev aluate the effects of different luteal phase support treatments. Each women receiv ed luteal support either with hCG, (after ov ulatory hCG injection, on day s 3, 6 and 9, injection of 1500 IU hCG), or with v aginal MP (200 mg vaginal MP progesterone suppository twice a day, starting 3 days after the ovulation triggering hCG injection) or no luteal support in consequent cycles with different orders. Thirty women underwent a total of 83 cycles using gonadotropin f or ovulation induction. Groups were compared according to their luteal phase lengths, midluteal progesterone lev els, complications, the time of hCG administration and estradiol value at the time of hCG administration. RESULTS: In the group of hCG luteal support, the midluteal progesterone (MLP) was signif icantly higher and the luteal phase length was significantly longer compared to MP and control group. Pregnancy rates were not statistically different f or the groups. CONCLUSION: Luteal phase support, during gonadotropin induced cycles, affect luteal phase positiv ely. But, no improvement in pregnancy rates was achiev ed with the use of luteal phase support.